Pojam pažnje u Bergsonovoj i Husserlovoj filozofiji - Losoncz, Mark (2021)
Članak se na komparativan način bavi pojmom pažnje u Bergsonovoj i Husserlovoj filozofiji. Posebna pažnja posvećena je njihovoj konfrontaciji sa psihološkim tumačenjima pažnje, kao i metodološkim aspektima njihovih teorija. Analizira se vitalnost, intencionalnost i temporalnost pažnje, imajući u vidu složenu terminološku pozadinu i kod Bergson i kod Husserla. Autor smatra da ih povezuje to što pažnju određuju kao dinamičnu unutrašnju modifikaciju, s različitim dimenzijama sadašnjosti, prošlosti i budućnosti. Istovremeno su uzete u obzir sličnosti i razlike u pogledu najvažnijih dilema.
The paper comparatively deals with the concept of attention in Bergson’s and Husserl’s philosophy. Special attention is devoted to their confrontation with psychological interpretations, as well as to methodological aspects of their theories. Analysed are the vitality, intentionality and temporality of attention by keeping in mind the complex terminological background in both Bergson and Husserl. The author holds that what connects them is that they both define attention as an inherent dynamic modification, with the different dimensions of presence, past and future. Similarities and differences are both taken into consideration concerning the most important dilemmas.
Bibliografske bilješke uz tekst.
Sažetak ; Abstract.
Keywords: Fenomenologija -- Pažnja -- Intencionalnost -- Temporalnost; Bergson, Henri -- Husserl, Edmund